Functional genomic profiling of O-GlcNAc reveals its context-specific interplay with RNA polymerase II - Sofia Rucli; Nicolas Descostes; Yulia Ermakova; Urvashi Chitnavis; Jeanne Couturier; Ana Boskovic; Matthieu Boulard (Genome Biology)
Abstract Background How reversible glycosylation of DNA-bound proteins acts on transcription remains scarcely understood. O-linked β-N-acetylglucosamine (O-GlcNAc) is the only known form of glycosylation modifying nuclear proteins, including RNA polymerase II (RNA Pol II) and many transcription factors. Yet, the regulatory function of the O-GlcNAc modification in mammalian chromatin remains unclear. Results Here, we combine genome-wide profiling of O-GlcNAc-modified proteins with perturbations of intracellular glycosylation, RNA Pol II-degron, and super-resolution microscopy. Genomic profiling of O-GlcNAc-modified proteins shows a non-random distribution across the genome, with high densities in heterochromatin regions as well as on actively transcribed gene promoters. Large-scale intersection of the O-GlcNAc signal at promoters with public ChIP-seq datasets identifies a high overlap with RNA Pol II and specific cofactors. Knockdown of O-GlcNAc Transferase (Ogt) shows that most direct target genes are downregulated, supporting a global positive role of O-GlcNAc on the transcription of cellular genes. Rapid degradation of RNA Pol II results in the decrease of the O-GlcNAc levels at promoters encoding transcription factors and DNA modifying enzymes. RNA Pol II depletion also unexpectedly causes an increase of O-GlcNAc levels at a set of promoters encoding for the transcription machinery. Conclusions This study provides a deconvoluted genomic profiling of O-GlcNAc-modified proteins in murine and human cells. Perturbations of O-GlcNAc or RNA Pol II uncover a context-specific reciprocal functional interplay between the transcription machinery and the O-GlcNAc modification.